Discovering the scholarship dimension of Ahmadiyya: Ahmadiyyaâs school on Indonesian Islamâs views - Thoriquttyas, Titis (ATTARBIYAH: Journal of Islamic Culture and Education, 2017)
AbstractIndonesian Islam ideas clearly elaborate the teachings of Islam which are promoting the tolerance, creating Muslim society which is harmonious and respecting the minority rights, such as on Ahmadiyyaâs issues. This article shows how Ahmadiyya communities are able to survive in Yogyakarta through educational institution and how the others society receive their existence peacefully. Limiting its scope on Ahmadiyyaâs school namely, Yayasan PIRI (Perguruan Islam Republik Indonesia) Yogyakarta which established on 1942 and it labeled as Ahmadiyyaâs school based on its history especially refers to Gerakan Ahmadiyya Indonesia. This paper drawn on the acceptability of Ahmadiyya-affiliated school around the society and its effort to negotiate their position used the Indonesian Islam ideas as the approach and the perspective. Furthermore, researcher will point out its uniqueness from the curriculum (learning materials), the educators and its learning methods in order to find the basic characteristics which it appropriate with what Indonesian Islam ideas could be contributedÂ Â Keywords: Indonesian Islam, Ahmadiyyaâs school, Yayasan PIRI YogyakartaAbstrakGagasan-gagasan Islam di Indonesia dengan jelas menguraikan ajaran ajaran Islam yang mempromosikan toleransi dan menciptakan masyarakat Muslim yang harmonis dan menghargai hak-hak minoritas, seperti isu-isu Ahmadiyah. Artikel ini menunjukkan bagaimana masyarakat Ahmadiyah dapat bertahan di Yogyakarta melalui institusi pendidikan dan bagaimana masyarakat lain menerima keberadaan mereka secara damai. Membatasi lingkupnya di sekolah Ahmadiyah yaitu Yayasan PIRI (Perguruan Islam Republik Indonesia) yang didirikan pada tahun 1942 dan diberi label sebagai sekolah Ahmadiyah berdasarkan sejarahnya, terutama mengacu pada Gerakan Ahmadiyah Indonesia. Makalah ini menggambarkan keberterimaan sekolah berafiliasi Ahmadiyah di sekitar masyarakat dan upayanya untuk menegosiasikan posisi mereka menggunakan gagasan-gagasan Islam Indonesia sebagai pendekatan dan perspektifnya. Selanjutnya, peneliti akan menunjukkan keunikannya dari kurikulum (materi pembelajaran), para pendidik dan metode belajarnya untuk mengetahui karakteristik dasar yang sesuai dengan gagasan Islam Indonesia.Â Kata kunci: Islam Indonesia, sekolah Ahmadiyyah, Yayasan PIRI Yogyakarta